An undiagnosed case of cervical ectopic pregnancy: A case report - HP, Sushma; BS, Girija; Suresh, Suchetha (Indian Journal of Case Reports, 2024)
Cervical ectopic pregnancy very rarely presents in the second trimester. A 35-year-old female was diagnosed with a rare case of cervical pregnancy intraoperatively at 18 weeks as it was undetected prior. Emergency laparotomy was done as she started bleeding torrentially, and a hysterectomy was done as postpartum hemorrhage was noted. The patient recovered in 1 day and was discharged on day 10 without any postoperative surgical complications.